QoS-Aware Splitting and Radio Resource Allocation for Machine Type Communications - Amitu, David Martin; Nyongarwizi Akol, Roseline; Nakeba, Peter (Computing and Communication Workshop and Conference (CCWC), 2018)
Machine Type Communications (MTC) networks need to resolve the key issues of massive access requirements, small data transmissions and diversity in Quality of service (QoS) requirements. The prominent approaches to address these challenges involve the use of MTC Gateways (MTCGs) as access points to the network, the use of MTC Devices (MTCDs) as relays and QoS clustering at the eNodeB. The MTCG-based approaches generally envision communication between MTCDs and the eNodeB through the MTCG only, for all MTCDs within the range of an MTCG. In this paper, we propose to divide MTCDs into delay-tolerant and delay-intolerant types, a process we coin ”MTCD splitting”. The proposed approach involves cluster formation, MTCD splitting and QoS-aware radio resource allocation. Our simulation results show better performance in terms of average throughput satisfaction and average QoS viola- tion probability when MTCD splitting is employed as compared to existing techniques without MTCD splitting.
Keywords: Quality of Service; Machine Type Communications; Radio Resource Allocation; MTCD Splitting; Cluster formation